Upgrading Karakteristik Biopelet Tandan Kosong Sawit Dengan Penambahan Oil Sludge Sebagai Co-Firing - Tengku Mukhlis; Idral Amri; Zuchra Helwani (Jurusan Teknik Kimia, Fakultas Teknik, UNRI, 2021)
Biopelet is one of the alternative fuels converted from biomass. Biomass which has great potential to be converted into biopelet is Empty Fruit Bunches (EFB). Such considerations make researchers interested in conducting a study on the use of EFB as an alternative fuel in the form of biopelets. In this research, we used torefaction and densification processes and the addition of oil sludge as a co-firing to increase the mass and energy density which had been a problem with the nature of EFB. The research procedure started from the raw material preparation stage, the EFB and oil sludge torefaction process and the bioepelet manufacturing stage. For fixed variables, the raw material size (EFB) is ± 15 mm , the raw material ratio is 70:30 (EFB: Oil Sludge), the torefaction temperature is 275 °C, the size of the biopelet diameter is 20 mm (ISO 17225). For 20 mesh particles, the N2 flow rate was 50 ml / minute, for the changing variables were the torefaction detention time of 30, 45 and 60 minutes, the pressing pressure was 30, 40 and 50 bar.The results showed that there was an effect of torefaction detention time which was directly proportional to the increase in proximate characteristics and calorific value of biopelets with the best results of 3.35% moisture content, 8.66% ash content, 9.50% volatile content, 78.49 %, fixed carbon content, and the calorific value of 4597.76 cal / g under the conditions of 60 minutes of torefaction detention time. There is an effect of pressing pressure which is directly proportional to the increase in the mechanical properties of the biopelet with the best results of density 1.148 gr / cm3, compressive strength 16.86 bar, and porosity of biopelet 13.33% under pressure conditions of 50 bar. The effect of adding oil Sludge as co-firing resulted in the calorific value of the biopelet being lower than the calorific value of EFB. This is because the calorific value of oil sludge is lower than the calorific value of EFB.